Computerised accounting using SYBIZ - Gerrard, Michael John; Dull, Richard B.;Wheeler, Patrick R. (New York : Prentice Hall, Inc., 1989)
This book aims to give accounting students a practical appreciation of accounting information systems.
Understanding information systems -- Organizing and managing information -- Enterprise risk management -- Business process -- Reporting -- Acquiring an AIS
Includes index.
Keywords: ACCOUNTING -- DATA PROCESSING